Virtual arthroplasty clinic: a single centre experience: commentary on progress, cost savings and patient retention. Issue 9 (21st June 2022) - Lim, Reuben; Du, John; Calligeros, Kosta
Abstract: Background: The COVID pandemic highlights utility of remote patient follow‐up. We observe a Virtual Clinic (VC) follow‐up model for arthroplasty used at a metropolitan hospital. Patients aged <70 that exhibit no issues in face‐to‐face review (F2F) progress to VC. We aimed to review VC's cost‐effectiveness, and identify potential improvements to patient allocation and retention. Method: A retrospective database was collated of all hip and knee joint arthroplasties performed at Frankston Hospital over a 12‐month period in 2017–2018. Patient encounters were followed from operation to discharge from F2F and, if appropriate, VC (involving imaging and a paper‐based qualitative questionnaire). VC attendance was compared to that of the year in which it was introduced (2014). The Clinical Costings Department provided average hospital spending for each of these modes of follow‐up. Results: Of 516 joint arthroplasties performed, 500 attended outpatient clinic (OPC). There were 884 F2F appointments (average 1.7 per person, range 0–12). One‐hundred‐and‐fifty‐four arthroplasties were correctly assigned to subsequent VC as per protocol (30%). Completed VC responses were received for 86 arthroplasties (56% response rate). In the period studied, VC attendance increased significantly compared to the year following introduction (36–56%, p  < 0.05), with the questionnaire revealing a high‐level of patient satisfaction for this method of follow‐up. Over the period studied, we estimate VC has saved $250 000 and 300 review hours from OPC. Conclusion: Implementing VC for follow‐up of arthroplasty may demonstrate a method of saving hospital resources. Appropriate early enrolment of patients to reduce F2F burden, and VC retention, should be encouraged. Abstract : Virtual Clinic follow‐up of arthroplasty was introduced to our institution in 2014. It demonstrates a method of saving hospital resources, and is especially of utility during a period of pandemic when remote follow‐up is desired.